Tissue Factor Pathway-Driven Initial Thrombin Generation is Associated with Hypercoagulability in Obesity - Kamikubo, Yuichi; Nagaya, Satomi; Inoue, Rina; Yamaguchi, Koichi; Morimoto-Kamata, Riyo; Inoue, Kenichi; Morishita, Eriko; Samad, Fahumiya; Ohkura, Naoki (Thrombosis and haemostasis, 2025)
Initial thrombin (FIIa) generated via the tissue factor (TF) pathway plays a crucial role in amplifying coagulation. There is growing evidence that the TF pathway might contribute to hypercoagulation in obesity. However, it is unclear if the initial generation of FIIa (TG) is associated with hypercoagulation in obesity due to the lack of appropriate assays. This study aims to evaluate association between TF pathway-driven initial TG and hypercoagulability in obesity.We measured the initial TG levels in plasma from male Tsumura Suzuki obese diabetes (TSOD) mice and overweight subjects using the highly sensitive TG assay. To induce initial TG, TF was added to the plasma and incubated at 37°C for up to 3 minutes. After quenching the TG, we quantified the generated FIIa by kinetically monitoring its amidolytic activity with a fluorogenic substrate.We observed that initial TG levels were significantly higher in TSOD mice ( = 31) compared with non-obese mice ( = 32). Even in the absence of exogenous TF, initial TG levels in obese mice and overweight individuals were elevated when procoagulant phospholipids were added alone. Moreover, the increased initial TG that the inhibitory anti-TF antibody abolished was detectable in reconstituted plasma including pellets prepared by high-speed centrifugation of plasma from obese mice, not in plasma supernatant. We attributed the promotion of the initial TG to the increase in procoagulant TF-bearing microvesicles in circulation. Based on the findings, measuring TF pathway-driven initial TG could be a valuable method for assessing hypercoagulability in obesity.